Estimasi Kandungan Karbon pada Sedimen Mangrove di Taman Hutan Raya Ngurah Rai, Pulau Bali - Falevi, Moh Rezasyah Falevi; Dharma, I Gusti Bagus Sila; Dirgayusa, I Gusti Ngurah Putra (Journal of Marine Research and Technology, 2026)
Mangrove ecosystems play a crucial role in climate change mitigation due to their exceptional ability to store carbon, particularly in sediment layers that can retain carbon for thousands of years. This study aimed to estimate vertical sediment carbon stocks in the mangrove ecosystem of Ngurah Rai Grand Forest Park (Tahura), Bali Island. Sampling was conducted at four stations using a purposive sampling method, with each station comprising three zones (front, middle, back) and four replicates per zone, resulting in 48 sediment samples. Each sample was sectioned into four depth intervals: 0–25 cm, 25–50 cm, 50–75 cm, and 75–100 cm. Environmental parameters such as pH, temperature, and salinity were measured, and sediment samples were analyzed using the Loss on Ignition (LOI) method. Carbon content was calculated by converting LOI to organic carbon, and combining it with bulk density values to estimate total carbon stock (in tons/ha). The results indicated variations in environmental parameters: pH ranged from 5.48 to 7.23, salinity from 2.06% to 5.90%, and temperature from 30.45°C to 31.58°C. Organic carbon content ranged from 3.66% to 5.64%, with the highest average found in the 50–75 cm depth layer. The central zone had the highest average carbon stock at 707.33 tons/ha, followed by the back (681.23 tons/ha) and front (543.63 tons/ha).